The Annulment of the 2024 Romanian Presidential Election. Between Constitutional Guardianship and Judicial Overreach (Journal of Legal Studies, 2025)
The article focuses on Ruling No. 32/2024 of the Constitutional Court of Romania, which annulled the first round of the presidential elections in response to intelligence revelations about large-scale foreign disinformation and covert digital campaigns. Based on Article 146(f) of the Constitution, the Court assumed its role as the guardian of electoral integrity ex officio, ordered a full rerun of the elections, and extended the term of the incumbent president. While the decision reflects a militant defence of democracy and resonates with European standards that allow for annulment in exceptional circumstances, it can also be argued that it exceeded the limits of legality. The Court’s reliance on declassified information, its succinct reasoning, and the absence of procedural safeguards raise questions about transparency, predictability, and thus the rule of law. Testing both sides of the coin - which the article attempts to tackle - can illustrate both the strength and fragility of Romanian constitutionalism, i.e., strong in its desire to defend democratic values, yet fragile in the absence of clear statutory and constitutional rules for such crises.